Are Cryptocurrencies Ḥaram? A Critical Analysis toward MUI’s Fatwā - Faizi (Faculty of Sharia IAIN Madura collaboration with The Islamic Law Researcher Association (APHI), 2023)
This paper critically examines the Indonesian Ulema Council's fatwā which prohibits cryptocurrency. The critique focuses on three aspects of the ban. The first is criticism for banning cryptocurrency which is considered to contain garar and ḍarār, and is contrary to Law No. 7 of 2011 and Bank Indonesia Regulation No. 17 of 2015. The second is criticism of the illegality of buying/selling cryptocurrency, which is positioned as a digital asset/commodity that contains garar, ḍarār, qimār, and does not meet the sil’ah criteria. The third is criticism of the permissibility of cryptocurrency as a commodity/asset when it fulfills the sil’aḥ criteria and has underlying and clear legal benefits to be traded. This study adopted a qualitative approach. The conclusion reveals that MUI's fatwā on cryptocurrencies was not built on solid legal reasoning and did not consider the benefits of technological advances. The MUI's fatwā is based on the principles of Islamic law, specifically garar, ḍarār, and qimār, which are used to evaluate the legality of trading commodities or digital assets, such as cryptocurrencies. However, it is important to note that the MUI's fatwā does not consider the potential benefits of cryptocurrencies, such as their use as a new form of investment and their potential to revolutionize industries by enhancing security, and efficiency, and creating new trading opportunities in the digital age. In terms of non-Sharia technology, it is seen as a tool that can be used for good or evil, and its permissibility depends on its use. Blockchain technology, which underpins cryptocurrencies, is considered acceptable because it makes transactions more secure and enables the use of smart contracts.